(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
Ijtihad In Islamic Legislation Had Remained The Most Important Instrument To Fulfill Its Validity, Immortality And Its Permanence. Also, It Is Considered As The Fundamental Method For Deduction (Istinbat) Based On The Qur’an And Sunnah. Numerous Ulama Of Islamic ’Principles Of Jurisprudence’ (Usul Al-Fiqh) Have Proposed Various Classifications Of The Qualities Required And Conditions To Be Met In Order For A Scholar To Be Considered A Mujtahid. However, In The 8th Century Imam Abu Ishaq Al-Shatibi (720-790) From Al-Andalus. Had Published A Famous Book Al-Muwafaqaat Fi Usul Al-Shariah, Which Has Established The Fundamental Basis Of Al-Maqasid. Al-Shatibi Through His Book Has Discussed The Requirements Of Being A Mujtahid In A Different Way; He Brought Together All The Conditions Under Two Main Rubrics: - A Deep Understanding Of The Arabic Language As It Was Understood By The Arabs During The Prophets Time. - A Real Mastery Of The Objectives Of The Shariah (Maqasid). This Study Examines The Above Matter In Detail; By Explaining The Reasons Which Convinces Al-Shatibi To Adopt This Opinion, Through The Extrapolation Of The Environment Of Al-Andalus, And Through His Various Writings.